SIPEMANDU-GPT: A DIGITAL TRAINING MODEL FOR 21ST CENTURY PE TEACHER PROFESSIONALISM - Rozi, Fatkhur; Priyono, Bambang; Putro, Baskoro Nugroho; Ratimiasih, Yulia; Prastiwi, Bertika Kusuma; Indarto, Pungki (Universitas Labuhanbatu, 2025)
Purpose – This study aims to develop a technology-based training design for physical education teachers through the Sipemandu-GPT model to enhance teacher professionalism.Methodology – This study employed a research and development (R&D) approach, adapting the Borg & Gall development model. The initial stage began with a preliminary study through interviews and observations involving KKGOMI teachers in Jepara Regency. The findings revealed that the training previously received was monotonous, lacked contextual relevance, and had not integrated technology. Consequently, a prototype training model based on blended learning was developed, combining online components (interactive modules, tutorial videos, virtual discussion forums) and offline components (teaching simulations, group discussions, written reflections).Findings – Validation by three experts indicated that the training design fell within the